Global burden of liver cancer attributable to drug use: trends from 1990 to 2021 and projections to 2040 - Cong Chen; Ying Zhou; Weiwei Gu; Zhuxin Gu; Pengfei Jia; Luyi Si; Suming Zhao; Hui Zhao (Discover Oncology)
Abstract Background Liver cancer (LC) is a major global health burden, with hepatocellular carcinoma (HCC) accounting for 75–85% of cases. Drug use, including legal and illicit substances, has emerged as a significant yet underrecognized risk factor for LC, contributing to viral hepatitis transmission, direct hepatotoxicity, and metabolic disorders. This study aims to assess the global and regional trends in drug-induced LC mortality and disease burden from 1990 to 2021 and project future trends up to 2040 using data from the Global Burden of Disease (GBD) 2021 database. Methods Utilizing GBD 2021 data, we analyzed age-standardized death rates (ASDR), disability-adjusted life years (DALYs), and estimated annual percentage changes (EAPC) to evaluate trends in drug-induced LC mortality globally and across Socio-Demographic Index (SDI) regions. The Bayesian Age-Period-Cohort (BAPC) model was employed to project future disease burden. Subgroup analyses were conducted using sex, age, and SDI categories to identify distinct patterns of change. Results From 1990 to 2021, global deaths from drug-induced LC increased nearly fourfold, with ASDR rising from 0.32 to 0.83 per 100,000 (EAPC = 1.81). DALYs increased significantly, from 9.60 to 20.42 per 100,000 (EAPC = 1.22). Women exhibited higher EAPC values for ASDR (2.36) and DALYs (1.87) compared to men, indicating that the relative rate of increase in the disease burden over time is greater for women. High SDI regions experienced the largest increases in ASDR and DALYs, while low SDI regions showed slower but steady growth. Projections suggest a plateau in ASDR and DALYs before 2030, followed by a decline by 2040. Conclusion The global burden of drug-induced LC has increased significantly, with notable disparities across regions and genders. High SDI regions face the fastest-growing burden, while low SDI regions experience rising mortality and morbidity. These findings underscore the need for targeted public health interventions to address drug use and LC prevention, particularly in high-risk populations and regions.